Profil De Résistance Des Mycobabcterium Tuberculosis Des Malades En Retraitement Dans La Région De Haute Matsiatra, Madagascar - Ravahatra Kiady; Rakotondrabe Iantsotiana Davidson; Rasoafaranirina Marie Odette; Tiaray Harison Michel; Nandimbiniaina Anjara; Rakotoson Joëlson Lovaniaina (European Scientific Journal, ESJ, 2017)
Introduction: Relapse, failure and defaulted treatment are a risk factor for Mycobacterium tuberculosis resistance to anti-tuberculosis. The objective of our study is to determine the resistance profile of Mycobacterium tuberculosis of patients in retreatment at the Haute Matriatra area. Method: This is a retrospective, descriptive study carried out on the basis of the data contained in the register of the Haute Matsiatra Regional Tuberculosis Laboratory of the University Hospital of Fianarantsoa, from May 2014 to December 2016 (31 months). We included patients with retreatment in the study. Results: We found 138 patients in retreatment. The average age was 39.32 years with a sex ratio of 2.11. Resistance to Rifampicin and Isoniazid was respectively 2.17% and 2.82%, The prevalence of multidrug-resistant tuberculosis was 0.72%. Conclusion: Tuberculosi resistance, monoresistance or multidrug resistance is a reality in the region of Haute Matsiatra with a prevalence that is still low, reflecting the effectiveness of the tuberculosis control program. However, monoresistances require special attention and monitoring to avoid the emergence of multidrug resistant strains.